Pengetahuan Didaktika Calon Guru Sekolah Dasar tentang Pecahan Ditinjau dari Teori Antropologi Didaktik - Putra, Zetra Hainul; Witri, Gustimal; Sari, Intan Kartika (Universitas Hamzanwadi, 2020)
Prospective elementary teachers (PET) are required to have sufficient mathematical and didactic knowledge about fractions, but many of them have difficulties explaining various concepts of fractions to students. Given the importance of prospective teachers’ knowledge of fractions, this study aims to investigate further the didactic knowledge of PETs’ didactic knowledge of fractions. Their knowledge is seen from their ability to construct contextual tasks about fractions based on number sense, problem-solving, mathematical literacy, and problem posing. PETs’ didactical knowledge is analyzed based on the anthropological theory of the didactic. This research method is qualitative with an internet-based research approach. The subjects of this study consist of 38 PsETs from a teacher education institution in Pekanbaru, Riau, Indonesia. The results of this study indicate that PsETs’ didactic knowledge of fractions is inappropriate, especially in the aspect of constructing contextual tasks about the division of fractions by fractions. PsETs tend to present the type of task associated with simple fraction operations and techniques in the form of standard algorithms. This study also indicates that PsETs’ theoretical knowledge is still limited to informal knowledge to support standard algorithms.